Some aspects of the case of Gurie Grosu, the ﬁrst Metropolitan of Bessarabia (Confluenţe Bibliologice, 2015)
The Metropolitan Gurie is „suspended” and retired by the Holy Synod in November 1936. The Bishop was acused in the Diocesan Assembly that he would have practiced „absolutist” management methods. Many intellectuals among whom were Nicolae Iorga, C. Cernăianu, Sebastian Teodorescu, Nicolae Popescu-Prahova defended Metropolitan Gurie. Being forced to retire from the position he held, Metropolitan Gurie Grosu will be set at Cernica Monastery, where he will be buried in November 14, 1943.
Keywords: Metropolitan Gurie Grosu (1877-1943); Bessarabian church; history of Bessarabia